The b chromosomes of prochilodus lineatus (Teleostei, characiformes) are highly enriched in satellite dnas - Stornioli, José Henrique Forte [UNESP]; Goes, Caio Augusto Gomes [UNESP]; Calegari, Rodrigo Milan [UNESP]; Dos Santos, Rodrigo Zeni [UNESP]; Giglio, Leonardo Moura [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP]; Penitente, Manolo; Porto-Foresti, Fábio [UNESP]; Utsunomia, Ricardo (MDPI, 2021)
B or supernumerary chromosomes are dispensable elements that are widely present in numerous eukaryotes. Due to their non-recombining nature, there is an evident tendency for repetitive DNA accumulation in these elements. Thus, satellite DNA plays an important role in the evolution and diversification of B chromosomes and can provide clues regarding their origin. The characiform Prochilodus lineatus was one of the first discovered fish species bearing B chromosomes, with all populations analyzed so far showing one to nine micro-B chromosomes and exhibiting at least three morphological variants (Ba, Bsm, and Bm). To date, a single satellite DNA is known to be located on the B chromosomes of this species, but no information regarding the differentiation of the proposed B-types is available. Here, we characterized the satellitome of P. lineatus and mapped 35 satellite DNAs against the chromosomes of P. lineatus, of which six were equally located on all B-types and this indicates a similar genomic content. In addition, we describe, for the first time, an entire population without B chromosomes.
Keywords: Concerted evolution; Curimbatá; Cytogenomics; Prochilodus; Repetitive DNA; Supernumerary chromosomes; Teleostei